Olfactory sensitivity to bile fluid and bile salts in the European eel (Anguilla anguilla), goldfish (Carassius auratus) and Mozambique tilapia (Oreochromis mossambicus) suggests a 'broad range' sensitivity not confined to those produced by conspecifics alone - Huertas, Mar (2014)
Teleosts have high olfactory sensitivity to bile salts. To assess whether this phenomenon is involved in intra-specific chemical communication alone, or is part of a more ‘broad range’ sensitivity to bile salts produced by heterospecifics, we investigated possible differences in the odour of bile between the sexes and among different species – the eel (Anguilla anguilla), goldfish (Carassius auratus) and Mozambique tilapia (Oreochromis mossambicus) – using the electro-olfactogram (EOG). We also identified the main bile constituents by liquid chromatography and mass spectrometry. There were marked differences in olfactory response of the eel to thin-layer chromatography fractions of bile from both sexes, and mature and immature conspecifics. Smaller differences were seen in the potency of fractions of bile from male and female goldfish and tilapia. Eels, goldfish and tilapia demonstrated similar olfactory sensitivity to bile from a range of different species, with no apparent correlation between the olfactory potency of bile and a phylogenetic closeness and/or similarity of diet of the donor to the receiver. The three species were able to detect odorants in thin-layer chromatography fractions of heterospecific bile even in the absence of activity in conspecific bile. Eels, goldfish and tilapia responded to both sulphated C27 bile salts (5-scymnol-sulphate and 5-cyprinol sulphate) and to taurine-conjugated C24 bile salts (taurochenodeoxycholic acid, taurolithocholic acid and taurocholic acid), irrespective of whether these bile salts were present in conspecific bile. Together, these results suggest that teleosts have a broad-range olfactory sensitivity to bile salts, with potential roles in both intra-specific chemical communication and in inter-specific interactions.